Egypt Economic Monitor, Spring 2015 : Paving the Way to a Sustained Recovery - World Bank (Washington, DC, 2015)
Egypt’s economic activity is gaining momentum. Growth accelerated to 5.6 percent during the first half of FY15, compared to a dismal 1.2 percent in the same period last year. The recent spike in economic activity reflects favorable base effects, but more importantly broad-based sector recovery, especially in tourism and manufacturing. On the demand side, growth continues to benefit from resilient consumption and government stimulus, supported by large financial inflows from Gulf States. In March 2015, Egypt held a high level Economic Development Conference, which culminated with the signing of sizeable investment deals worth US$36 billion, securing external financing worth US$24 billion, and the announcement of a new Gulf support package worth US$12.5 billion. This will boost the ongoing economic recovery and facilitate efforts to achieve macroeconomic stability. Annual growth is expected to double to 4.3 percent in FY15, and should increase further thereafter, compared to the muted growth of 2 percent during FY11-FY14. The International Monetary Fund (IMF) conducted its article four consultation in November 2014 and the final report generally commended the authorities’ medium term plans while highlighting some risks including slippage in implementing reforms and a large external financing gap. Egypt’s main risk is to sustain the ongoing economic recovery which requires improved security. Notwithstanding the authorities’ ambitious fiscal consolidation plan, the deficit and debt aggregates will remain high and unsustainable. Further, there are risks of policy slippage as some details and the exact timing of policy measures are still missing and implementation capacity remains a challenge. Further, sustaining the reform pace requires efficient and well-targeted safety nets, which might take time to build. Finally, there is significant uncertainty regarding the financing of the announced mega-projects and the potential contingent liabilities that may arise.